Prevalence of anemia and deficiency of iron, folic acid, and zinc in children younger than 2 years of age who use the health services provided by the Mexican Social Security Institute - González-Unzaga Marco; Ramos Rosa I; Martínez-Andrade Gloria; Turnbull Bernardo; Muñoz Sergio; Méndez-Ramírez Ignacio; Flores-Huerta Samuel; Flores-Hernández Sergio; Duque Ximena; Mendoza María E; Martínez Homero (BMC, 2007)
Abstract Background In Mexico, as in other developing countries, micronutrient deficiencies are common in infants between 6 and 24 months of age and are an important public health problem. The objective of this study was to determine the prevalence of anemia and of iron, folic acid, and zinc deficiencies in Mexican children under 2 years of age who use the health care services provided by the Mexican Institute for Social Security (IMSS). Methods A nationwide survey was conducted with a representative sample of children younger than 2 years of age, beneficiaries, and users of health care services provided by IMSS through its regular regimen (located in urban populations) and its Oportunidades program (services offered in rural areas). A subsample of 4,955 clinically healthy children was studied to determine their micronutrient status. A venous blood sample was drawn to determine hemoglobin, serum ferritin, percent of transferrin saturation, zinc, and folic acid. Descriptive statistics include point estimates and 95% confidence intervals for the sample and projections for the larger population from which the sample was drawn. Results Twenty percent of children younger than 2 years of age had anemia, and 27.8% (rural) to 32.6% (urban) had iron deficiency; more than 50% of anemia was not associated with low ferritin concentrations. Iron stores were more depleted as age increased. Low serum zinc and folic acid deficiencies were 28% and 10%, respectively, in the urban areas, and 13% and 8%, respectively, in rural areas. The prevalence of simultaneous iron and zinc deficiencies was 9.2% and 2.7% in urban and rural areas. Children with anemia have higher percentages of folic acid deficiency than children with normal iron status. Conclusion Iron and zinc deficiencies constitute the principal micronutrient deficiencies in Mexican children younger than 2 years old who use the health care services provided by IMSS. Anemia not associated with low ferritin values was more prevalent than iron-deficiency anemia. The presence of micronutrient deficiencies at this early age calls for effective preventive public nutrition programs to address them.